RETRACTED: Recent trends in the use of bacteriophages as replacement of antimicrobials against food-animal pathogens - Zia, Sana; Alkheraije, Khalid A. (Frontiers in Veterinary Science, 2023)
There is a major public health impact associated with foodborne illnesses around the globe. Additionally, bacteria are becoming more resistant to antibiotics, which pose a global threat. Currently, many scientific efforts have been made to develop and implement new technologies to combat bacteria considering the increasing emergence of multidrug-resistant bacteria. In recent years, there has been considerable interest in using phages as biocontrol agents for foodborne pathogens in animals used for food production, as well as in food products themselves. Foodborne outbreaks persist, globally, in many foods, some of which lack adequate methods to control any pathogenic contamination (like fresh produce). This interest may be attributed both to consumers' desire for more natural food and to the fact that foodborne outbreaks continue to occur in many foods. Poultry is the most common animal to be treated with phage therapy to control foodborne pathogens. A large number of foodborne illnesses worldwide are caused by Salmonella. spp and Campylobacter, which are found in poultry and egg products. Humans and animals can be prevented and controlled from various infectious diseases using conventional bacteriophage-based therapy. In this context, describing bacteriophage therapy based on bacterial cells may offer a breakthrough for treating bacterial infections. Large-scale production of pheasants may be economically challenging to meet the needs of the poultry market. It is also possible to produce bacteriophage therapy on a large scale at a reduced cost. Recently, they have provided an ideal platform for designing and producing immune-inducing phages. Emerging foodborne pathogens will likely be targeted by new phage products in the future. Bacteriophages (phages) have been proposed as an alternative strategy to antibiotics for poultry in this context, and thus for public health and food safety.